Yemen's Cholera Epidemic Is a One Health Issue - Qin Xiang Ng; Michelle Lee Zhi Qing De Deyn; Wayren Loke; Wee Song Yeo (Korean Society for Preventive Medicine, 2020)
Yemen has been faced with the worst cholera epidemic of modern times, with more than 1 million suspected cases and 3000 deaths at the time of writing. This problem is largely due to the longstanding civil war between pro-government forces and the Houthi armed movement, which has severely damaged already vulnerable sanitation and healthcare facilities and systems in the country. It is further compounded by a dire lack of basic amenities, chronic malnutrition, and unfavourable weather conditions. Another contributory component may be aerial transfer by cholera-infected chironomid insects. To contain the spread of cholera in Yemen, a nation-wide armistice should be negotiated, and national and local committees must be convened to coordinate efforts on the ground. Community isolation facilities with proper sanitation, reliable disposal systems, and a clean water supply should be set up to isolate and treat sick patients. The continuity of vaccination programmes should be ensured. Public health campaigns to educate local communities about good hygiene practices and nutrition are also necessary. The One Health paradigm emphasizes a multi-sectoral and transdisciplinary understanding and approach to prevent and mitigate the threat of communicable diseases. This paradigm is highly applicable to the ongoing cholera crisis in Yemen, as it demands a holistic and whole-of-society approach at the local, regional, and national levels. The key stakeholders and warring parties in Yemen must work towards a lasting ceasefire during these trying times, especially given the extra burden from the mounting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak worldwide.